2021
DOI: 10.1021/acs.analchem.1c03102
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Luminol/Dissolved Oxygen/Fe@Fe2O3 Nanowire Ternary Electrochemiluminescence System Combined with Highly Efficient Strand Displacement Amplification for Ultrasensitive microRNA Detection

Abstract: Herein, a versatile ECL biosensor was fabricated for ultrasensitive detection of microRNA-21 (miRNA-21) from cancer cells based on a novel H 2 O 2 -free electrochemiluminescence (ECL) system (luminol/dissolved oxygen/Fe@Fe 2 O 3 nanowires). Compared with the previously reported coreaction accelerator that needed a negative potential to produce reactive oxygen species (ROS), these newly discovered Fe@Fe 2 O 3 nanowires could generate ROS in the detection solution immediately without the application of voltage, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 35 publications
2
30
0
Order By: Relevance
“…Meanwhile, Figure 6B shows that luminol (curve a) had a small oxidation peak at 0.5 V, and the current of the oxidation peak increased in the presence of ferrocene (curve b). The ECL behaviour was due to that luminol was electrooxidized to luminol radical L⋅ − , and dissolved oxygen was reduced to O 2 ⋅ − ; then L⋅ − reacted with O 2 ⋅ − to generate excited‐state 3‐aminophthalate (AP 2−* ), which underwent a radiative reaction and released luminescence [26]. In the presence of Fc, Fc was electrooxidized to Fc + at low potential, and Fc + oxidized luminol to a high energy state, which was favourable to the following electro‐oxidation of luminol and subsequent ECL reaction with dissolved oxygen, and the ECL signal was enhanced.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, Figure 6B shows that luminol (curve a) had a small oxidation peak at 0.5 V, and the current of the oxidation peak increased in the presence of ferrocene (curve b). The ECL behaviour was due to that luminol was electrooxidized to luminol radical L⋅ − , and dissolved oxygen was reduced to O 2 ⋅ − ; then L⋅ − reacted with O 2 ⋅ − to generate excited‐state 3‐aminophthalate (AP 2−* ), which underwent a radiative reaction and released luminescence [26]. In the presence of Fc, Fc was electrooxidized to Fc + at low potential, and Fc + oxidized luminol to a high energy state, which was favourable to the following electro‐oxidation of luminol and subsequent ECL reaction with dissolved oxygen, and the ECL signal was enhanced.…”
Section: Resultsmentioning
confidence: 99%
“…The nucleic acids skills contained HCR, [161] DNAzyme, [162] circle rolling amplification, [163] catalytic hairpin assembly (CHA), [164] and strand displacement amplification (SDA). [165] Lin et al also developed the photoelectrochemical biosystems via the alternation of photosensitive materials. Previously, his group identified that Cu(I)-formed coordination polymer exhibited visible-light absorption and its proper band edge position enables attractive performance forming p-n junction with TiO 2 .…”
Section: Electrochemical Sensorsmentioning
confidence: 99%
“…Further, with the aid of a highly efficient SDA amplification strategy in the solution, ultrasensitive detection for miRNA was realized with a detection limit down to 52.5 aM. 66…”
Section: Electrochemiluminescence (Ecl) Sensingmentioning
confidence: 99%